2021
DOI: 10.3390/g12040089
|View full text |Cite
|
Sign up to set email alerts
|

Social Learning Strategies and Cooperative Behaviour: Evidence of Payoff Bias, but Not Prestige or Conformity, in a Social Dilemma Game

Abstract: Human cooperation, occurring without reciprocation and between unrelated individuals in large populations, represents an evolutionary puzzle. One potential explanation is that cooperative behaviour may be transmitted between individuals via social learning. Using an online social dilemma experiment, we find evidence that participants’ contributions were more consistent with payoff-biased transmission than prestige-biased transmission or conformity. We also found some evidence for lower cooperation (i) when exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 102 publications
(150 reference statements)
0
5
0
Order By: Relevance
“…3 and Fig. 4c), mirroring the human tendency to "copy" (here rather "learn from") the suc-cessful 24,25 . Nevertheless, it remains an open question how sensitive participants can be to others' perceived skill in this task, and in what way this would influence their decisionmaking.…”
Section: Limitations and Future Directionsmentioning
confidence: 77%
See 2 more Smart Citations
“…3 and Fig. 4c), mirroring the human tendency to "copy" (here rather "learn from") the suc-cessful 24,25 . Nevertheless, it remains an open question how sensitive participants can be to others' perceived skill in this task, and in what way this would influence their decisionmaking.…”
Section: Limitations and Future Directionsmentioning
confidence: 77%
“…How such varying correlations between participants would affect how social information is used remains an open question. Given prior research showing that humans are quite capable of adjusting their social learning based on the skill of the observed individual 2,25,26 , it seems reasonable to assume they could adjust to higher or lower levels of correlation as well. It would be interesting to see if this would lead to only learning from the most closely correlated individual, or from all sources but with higher assumed noise for lower correlations.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-culturally, there is evidence that altruism can be influenced by context-specific social norms (Henrich et al, 2010 ). However, when also shown the payoffs of others, individuals appear to engage in payoff-biased copying and reduce their altruism (Burton-Chellew et al, 2017b ; Burton-chellew & Amico, 2021 ; Molleman et al, 2014 ; Watson et al, 2021 ). In ultimatum games, a theoretical model showed that a form of payoff-biased social learning resulted in average offerings of between 40 and 50% (Zhang, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the information source, we consider conformity (or copy-the-majority; Boyd & Richerson, 1985 ; Morgan & Laland, 2012 ) and copy-the-successful (McElreath & Henrich, 2003 ; Sarin & Dukas, 2009 ) social learning strategies. Both have been documented in a variety of contexts (reviewed in Kendal et al, 2018 ; Kendal & Watson, 2023 ), including studies investigating altruism (Burton-Chellew et al, 2017a ; Burton-Chellew & Amico, 2021 ; Watson et al, 2021 ). Note, however, that some studies have found no effect of information source on transmission.…”
Section: Introductionmentioning
confidence: 99%